Polygenic risk for schizophrenia, transition and cortical gyrification: a high-risk study. Issue 9 (25th October 2017) - Neilson, E.; Bois, C.; Clarke, T.-K.; Hall, L.; Johnstone, E. C.; Owens, D. G. C.; Whalley, H. C.; McIntosh, A. M.; Lawrie, S. M.
Abstract: Background: Schizophrenia is a highly heritable disorder, linked to several structural abnormalities of the brain. More specifically, previous findings have suggested that increased gyrification in frontal and temporal regions are implicated in the pathogenesis of schizophrenia. Methods: The current study included participants at high familial risk of schizophrenia who remained well ( n = 31), who developed sub-diagnostic symptoms ( n = 28) and who developed schizophrenia ( n = 9) as well as healthy controls (HC) ( n = 16). We first tested whether individuals at high familial risk of schizophrenia carried an increased burden of trait-associated alleles using polygenic risk score analysis. We then assessed the extent to which polygenic risk was associated with gyral folding in the frontal and temporal lobes. Results: We found that individuals at high familial risk of schizophrenia who developed schizophrenia carried a significantly greater burden of risk-conferring variants for the disorder compared to those at high risk (HR) who developed sub-diagnostic symptoms or remained well and HC. Furthermore, within the HR cohort, there was a significant and positive association between schizophrenia polygenic risk score and bilateral frontal gyrification. Conclusions: These results suggest that polygenic risk for schizophrenia impacts upon early neurodevelopment to confer greater gyral folding in adulthood and an increased risk of developing the disorder.